To what degree does a high-energy aurora destroy F-region irregularities? - Ivarsen, Magnus F.; St-Maurice, Jean-Pierre; Jin, Yaqi; Park, Jaeheung; Buschmann, Lisa M.; Clausen, Lasse B. N. (Frontiers in Astronomy and Space Sciences, 2024)
Using two separate databases of in situ ionospheric observations, we present case studies and perform a statistical investigation of the link between energetic precipitating particles during the polar night and high-latitude F-region steepening density spectra. Our study covers approximately 3 years of data obtained near the peak of the 24th solar cycle from four Defense Meteorological Satellite Program satellites and from the European Space Agency’s Swarm satellites. Focusing on the midnight sector of the auroral oval, we found that there is a near-perfect co-location between high-energy precipitating particles and occurrence of dissipating F-region plasma density spectra. This is because the precipitating energy flux strongly enhances the E-region Pedersen conductivity, allowing fast and efficient dissipation of kilometer-scale F-region irregularities. Spectra that are possibly non-dissipating are in turn co-located with the distribution of soft electron precipitation. Together, dissipating and non-dissipating density spectra constitute two distinct irregularity regimes. Surprisingly, we also found that efficient dissipation notwithstanding, high-energy precipitating particles cause a net increase in the F-region irregularity power, suggesting that growth and dissipation are interlinked and that some of the observed F-region irregularities may conceivably be generated in the E region. This work is expected to be beneficial for the classification of F-region in situ density spectra and suggests that such density spectra can be used to infer the presence of high-energy or low-energy precipitations based on spectral properties.